Sinonasal diffuse large B-cell lymphoma in a patient with Wiskott–Aldrich syndrome: A case report and literature review - Sun, Xiwen; Luo, Chunyu; Tang, Ru; Mao, Song; Zhu, Ying; Fei, Chonghui; Wang, Mengyu; Tan, Shaolin; Zhang, Shiyao; Zhou, Jiayao; Lin, Hai; Li, Zhipeng; et al. (Frontiers in Immunology, 2023)
Wiskott-Aldrich syndrome (WAS) is a rare primary immunodeficiency disease with a predisposition towards autoimmunity and lymphoproliferative diseases. It is reported that non-Hodgkin lymphoma (NHL) was the predominant form of malignant tumors in patients with WAS. Diffuse large B-cell lymphoma (DLBCL) is one of the most common types of NHL while it is uncommon to occur in paranasal sinuses and especially when associated with WAS. In this article, we report a unique case of WAS associated with DLBCL in paranasal sinuses and review the major publications of WAS-related lymphomas occurred in head and neck area. This report extends the treatment of WAS-related lymphomas and highlights the importance of recognition for sinonasal lymphomas in WAS patients presenting with sinusitis.